Writing Skill: An Instructional Overview - Gautam, Pitamber (Journal of NELTA Gandaki, 2019)
Writing skill is a product of ingenuity carved through knowledge, learning, creativity and intellectual uprightness. An individual with sound writing skills is regarded high in dignity and receives elevated opportunities everywhere in competitive examinations, job opportunities, promotions and social services. Regarding the discipline of teaching and learning a language, proficiency in writing skill deserves an irrelative significance. In spite of being an unsurmountably significant skill, numerous learners and pedagogues still seem to be bewildering for specifying the actual crux of theoretical knowledge and pedagogical procedures of writing in a compact document. In order to bridge up this goal, this study attempts to open some pertinent horizons in terms of its objectives, approaches, types, components and cannons for evaluation through document analysis method, a major component of qualitative research design. Fairly a large number of document based views, ideas, opinions, definitions, approaches and guidelines have been analyzed critically. Obviously, the resources covered in the review, results and discussion section would prove to be reliable sources for the prospective learners and researchers. The study concludes that the teachers and syllabus designers have to keep themselves up-to-date with process based current approaches, methods and techniques alongside their theoretical and practical foundations. The most noteworthy insight drawn is that there are not any specific methods and techniques comprehensive enough to capture all the facets of teaching writing skill. Therefore, the teacher has to select and implement the best ones from a wide range of methods and techniques eclectically by musing on the classroom stakeholders deeply.